The Influence Of Social Media Marketing Effort On Purchase Decisions Mediated By Brand Trust In Shrimp Farmers - Yoppie Budiono; Teofilus Teofilus; Metta Padmalia (UNIVED Press, 2025)
The aim of this research is to investigate the influence of social media marketing effort on consumer purchase decisions in the plastic geomembrane industry. Apart from that, it is also to test whether brand trust mediates the relationship between social media marketing effort and purchase decisions. Necessary data was gathered from consumers of geomembrane plastic JEMPOL via a quantitative online survey. After obtaining the desired responses, the data was analyzed by the SPSS – Statistical Package for the Social Science and JASP - Jeffreys's Amazing Statistics Program software. The results confirmed the significance of brand trust in predicting purchase decision. Above that, this study provides a good understanding of the consumer behavior of geomembrane plastic JEMPOL and a new perspective in the geomembrane plastic industry.